Medical co‐morbidities and practice. (May 2014) - Kulkarni, R.; Mauser‐Bunschoten, E. P.; Stedman, C.; Street, A.
Summary: All‐oral treatments of hepatitis C (HCV) have been trialled in patients with hereditary bleeding disorders and found to be effective. Further refinements of dosing and duration are being established. Importantly for patient acceptability these regimens are interferon‐free. Cohort studies in older patients with haemophilia direct the need for attention to weight control, exercice, assessment of cardiovascular risk, especially hypertension and detection of osteoporosis. Where patients live a long way from a comprehensive care centre, telemedicine connections can engage centre experts with the patient and his/her local practitioners in devising and monitoring care plans